Crystallisation Kinetics of a β-Spodumene-Based Glass Ceramic - Oscar Rubem Klegues Montedo; Dachamir Hotza; Antonio Pedro Novaes de Oliveira; Robert Meszaros; Nahum Travitzky; Peter Greil (Advances in Materials Science and Engineering)
LZSA (Li2O-ZrO2-SiO2-Al2O3) glass ceramic system has shown high potential to obtain LTCC laminate tapes at low sintering temperature (<1000°C) for several applications, such as screen-printed electronic components. Furthermore, LZSA glass ceramics offer interesting mechanical, chemical, and thermal properties, which make LZSA also a potential candidate for fabricating multilayered structures processed by Laminated Objects Manufacturing (LOM) technology. The crystallization kinetics of an LZSA glass ceramic with a composition of 16.9Li2O⋅5.0ZrO2⋅65.1SiO2⋅8.6Al2O3 was investigated using nonisothermal methods by differential thermal analysis and scanning electronic microscopy. Apparent activation energy for crystallization was found to be in the 274–292 kJ⋅mol−1 range, and an Avrami parameter n of 1 was obtained that is compared very favorably with SEM observations.